The Polish linguistic test review in the assessment of Central Auditory Processing Disorders - Mąka, Joanna (Investigationes Linguisticae, 2009)
The issue presented here dwells on linguistic tests as universal materials used in detection of hearing deficits and as a possibility of hearing training in all stages of speech perception. The article ranges the tests of which usage is important in case of the Central Auditory processing Disorder. The auditory impairments like CAPD are seldom phenomena from which suffer 10 % of adults and 2-3% of children. Everybody who frequently mishears words, misses instructions, has difficulty rapidly and accurately processing verbal information, has trouble with the prosodic or musical aspects of speech, or has noticeable difficulty hearing in background noise, should be suspected of having an auditory processing deficit and should receive a thorough evaluation. In other words, problem with interpreting and analyzing the sensory information received via auditory pathway is called Central Auditory Processing Disorder and needs a proper battery of audiologic tests. Criteria, which should be applied while preparing central auditory tests, have recently undergone practical practical and theoretical verification. Difficulty in formulating a representative , reliable and precise test is caused by many variables which appear by necessity of taking the phonetic and acoustic structure into consideration. Tests used in medical examination in order to diagnose Central Auditory Processing Disorders are classified into two major categories: Psychoacoustic tests and Electrophysiologic tests.